A CASE OF MULTIPLE PRIMARY CANCER: SYNCHRONOUS CERVICAL ADENOCARCINOMA AND SQUAMOUS CELL OVARIAN CARCINOMA - S. V. Molchanov; L. A. Kolomiets; O. V. Shpileva; N. G. Trukhacheva; E. A. Fesik; V. M. Perelmuter (Сибирский онкологический журнал, 2016)
A rare clinical case of synchronous cervical adenocarcinoma and primary squamous cell ovarian carcinoma has been presented. Epidemiological and treatment aspects have been analyzed.